Pengaruh Variasi Kedalaman Potong terhadap Gaya Potong dan Temperatur pada Proses Bubut Baja AISI 304 Berdasarkan Metode Elemen Hingga - Mudmainah, Putri Hana Widyaning; Susanto, Agus; Ciptaningrum, Adiratna; Alfiyani, Risma; Wicaksono, Ramadhana Eka (Rekayasa Material, Manufaktur dan Energi, 2023)
Cutting forces are parameters that can be used to optimize the machining process, analyze power consumption, and affect temperature during the lathe process. Measurement of cutting forces using a dynamometer and temperature using a thermocouple is quite expensive. This article discusses the effect of machining parameters on cutting force and temperature on AISI 304 steel workpiece material with carbide insert tool. The method used to analyze cutting forces and temperatures is based on the finite element method (FEM). The results show that the cutting force fluctuates due to the influence of depth of cut. The greater the value of the depth of cut used, the greater the axial cutting force and tangential cutting force. While the temperature does not change due to variations in depth of cut. Cutting speed variations do not significantly affect the cutting force, but affect the cutting time and temperature. The greater the cutting speed value used, the greater the temperature produced and the less cutting time required.